Evaluation of glass forming ability in ternary Ni62(Nb, Ta)38 alloys. (September 2017) - Yu, P.; He, M.K.; Wu, Z.M.; Wen, L.; Zeng, Z.Y.; Xia, L.
Abstract: The parameter γ ∗ we previously defined has been proved to be valid in predicting the better glass former in several binary alloy systems, but is hard to be applied in the multi-component alloys because the phase diagrams of these alloys are usually not well constructed. In the present work, we attempt to extend the application of parameter γ ∗ to a ternary alloy system and predict the better glass former in the Ni62 Nb38-x Tax (x = 5, 10, 15, 20, 25, 30, 35) alloys based on the systematic investigation on the phase evolution from Ni62 Nb38 to Ni62 Ta38 . The prediction has been confirmed by the experimental results, indicating the validity of the parameter γ ∗ in the Ni62 (Nb, Ta)38 ternary alloys. Highlights: The better glass former in the ternary Ni62 (Nb, Ta)38 alloys was predicted by the parameter γ ∗ . Ni62 Nb23 Ta15 is the best glass former in the Ni62 Nb38-x Tax alloys. Parameter γ ∗ is effective to identify better glass former in the ternary alloy systems.